2002
DOI: 10.1038/sj.gt.3301735
|View full text |Cite
|
Sign up to set email alerts
|

Polyethylenimine-mediated cellular uptake, nucleus trafficking and expression of cytokine plasmid DNA

Abstract: Although polyethylenimine (PEI) Cytokine gene therapy has been studied for the treatment of cancer and infectious diseases, and for the development of effective molecular adjuvants.1 Recently, cytokine genes have been administered in nonviral gene delivery systems to increase the stability and the efficiency of cytokine gene expression. Lipid-complexed forms of human interleukin-2 gene are currently in phase I clinical trial for prostate cancer.2 Polyvinyl pyrrolidoneformulated cytokine genes resulted in hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
65
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(69 citation statements)
references
References 17 publications
3
65
0
1
Order By: Relevance
“…The radioactivity distribution pattern concurs with that of PEI-derived polyplexes, which are reported as one of the most effective nonviral vectors in vivo. 37 Luciferase expression levels revealed that all complexes were able to enhance the transfection efficiency to the same level. Introduction of an NLS sequence did not lead to further improvement of the transfection efficiency, suggesting that translocation to the nucleus is not rate-limiting.…”
Section: Discussionmentioning
confidence: 99%
“…The radioactivity distribution pattern concurs with that of PEI-derived polyplexes, which are reported as one of the most effective nonviral vectors in vivo. 37 Luciferase expression levels revealed that all complexes were able to enhance the transfection efficiency to the same level. Introduction of an NLS sequence did not lead to further improvement of the transfection efficiency, suggesting that translocation to the nucleus is not rate-limiting.…”
Section: Discussionmentioning
confidence: 99%
“…The underlying cause is probably a welldocumented phenomena of the intracellular plasmid degradation, spontaneous loss, and dilution during cell divisions in transiently transfected cells. 55,56 We have demonstrated that the sensor and the amplifier constructs were present and activated in the same cell 48 hr after the transfection ( Figure S3C). However, as expected, the plasmid copy number per cell dropped within 5 days after transfection, but nevertheless, the amplifier construct, which was introduced at the lowest amounts, and the inducible OFF-switch representing a safety mechanism, were still present at that time ( Figure S7C).…”
Section: Discussionmentioning
confidence: 89%
“…Many preclinical studies have shown a significant increase in immunogenicity of DNA-PEI conjugates, as well as a dramatic reduction in toxicity as the molecular weight of the polymer is reduced. 22,23,25,26,38 The use of PEI in clinical vaccination has been approved by the regional regulatory authorities (State Committee on Science and Technology of the Republic of Belarus).…”
Section: Discussionmentioning
confidence: 99%
“…Polyethylenimine (PEI) is a cationic polymer commonly used as a transfection reagent in vitro 22 and synthetic vehicle for transgene and DNA vaccine delivery in vivo. [23][24][25] It has been shown that T-cell immune responses can be increased by 20-fold with DNA-PEI complexes compared with responses elicited by intramuscular injections with naked DNA.…”
Section: Introductionmentioning
confidence: 99%